2022
DOI: 10.1111/tpj.15912
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione degradation activity of γ‐glutamyl peptidase 1 manifests its dual roles in primary and secondary sulfur metabolism in Arabidopsis

Abstract: Glutathione (GSH) functions as a major sulfur repository and hence occupies an important position in primary sulfur metabolism. GSH degradation results in sulfur reallocation and is believed to be carried out mainly by c-glutamyl cyclotransferases (GGCT2;1, GGCT2;2, and GGCT2;3), which, however, do not fully explain the rapid GSH turnover. Here, we discovered that c-glutamyl peptidase 1 (GGP1) contributes to GSH degradation through a yeast complementation assay. Recombinant proteins of GGP1, as well as GGP3, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…The sulfur metabolic process has been widely considered as an important part of plant growth and development. Cys, regarded as an intermediate product of sulfur metabolism, plays essential roles. However, no NIR fluorescent probes have been reported for monitoring Cys in plants.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur metabolic process has been widely considered as an important part of plant growth and development. Cys, regarded as an intermediate product of sulfur metabolism, plays essential roles. However, no NIR fluorescent probes have been reported for monitoring Cys in plants.…”
Section: Resultsmentioning
confidence: 99%
“…The transcript levels of the three isoforms of APR, the key enzyme in the reduction of sulfate, were not significantly affected by the disruption of the OASC gene, neither in the shoot nor in the root ( Figure 3 ). The expression of two markers of sulfur deficiency, SDI1 , which is involved in GLS regulation, and GGTC2;1 , which contributes to GSH degradation, were also not different in oasC compared to Col-0 [ 4 , 18 ]. In addition, the expression levels of the major isoforms of OAS-TL were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Taking together, our results indicate that AtGGTs are involved in the apoplastic (AtGGT1) and vacuolar (AtGGT4) catabolism of GSH Sconjugates of xenobiotics (GS-bimane), whereas AtPCSs are involved in their cytoplasmic degradation (Figure 7). While GGTs control GSH and GSH S-conjugate degradation in the apoplastic and vacuolar compartments, alternative cytosolic pathways of GSH catabolism by means of γ-glutamylcyclotransferase (GGC T, EC2.3.2.4) and γ-glutamylpeptidase (GGP,EC3.4.19.16) have been proposed to dominate these processes in the cytosol (Ito et al 2022;Kumar et al 2015;Ohkama-Ohtsu et al 2008;Paulose et al 2013). Arabidopsis contains three potential GGC T genes (GGCT1=At1g44790, GGCT2;1=At5g26220, GGCT2;2=At4g31290) encoding proteins that cleave GSH when overexpressed in yeast (Kumar et al 2015;Paulose et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…GGP1 and GGP3 were originally shown to be involved in the processing of GSH S-conjugates in the glucosinolate and camalexin pathways (Geu-Flores et al 2011. However, Ito et al (2022) have recently reported that recombinant GGP1 and GGP3 are capable of hydrolyzing the γ-glutamyl residue of GSH in vitro. Moreover, yeast complementation assays, and the characterization of ggp1 mutants suggest that GGP1 play a major role in cytoplasmic degradation of GSH in Arabidopsis (Ito et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation